Mercury speciation and Hg stable isotope ratios in sediments from Amazon floodplain lakes—Brazil. (10th December 2017) - Araujo, Beatriz Ferreira; Hintelmann, Holger; Dimock, Brian; de Lima Sobrinho, Rodrigo; Bernardes, Marcelo Correa; de Almeida, Marcelo Gomes; Krusche, Alex V.; Rangel, Thiago Pessanha; Thompson, Fabiano; de Rezende, Carlos Eduardo
Abstract: Hg concentrations and isotope ratios were measured to better characterize the mercury dynamics related to Hg cycling in Amazon floodplain lakes. We collected sediments, suspended particulate material (SPM), and plankton from floodplain lakes and compared then to sediments from rivers and soils of the central Amazon basin by measuring concentrations of total Hg (THg) and methylmercury (MMHg), and mercury isotope ratios. Concentrations of THg and MMHg in the lake sediments ranged to 69–109 ng g −1 and 0.62–4.78 ng g −1, respectively. A positive correlation between THg and MMHg in soils and sediments suggest that inorganic Hg in this system is highly bioavailable and readily converted to MMHg. δ 202 Hg values ranged from −1.40‰ to −0.89‰ and Δ 199 Hg from −0.34‰ to −0.18‰. These values were comparable to those measured in riverine sediments (−2.14‰ to −1.23‰ and −0.51‰ to −0.05‰), suggesting a contribution of riverine sediments to lake sediments, at least during the season of rising waters, during which lake samples were collected. SPM on the other hand was much elevated in THg (590–1066 ng g −1 ) and showed more negative δ 202 Hg (−3.00 to −2.15), similar to those found in soils (−2.99‰ to −2.17‰), suggesting that Hg in SPM may originate from erosion of floodplain soils.